Development of duplex real‐time polymerase chain reaction for simultaneous detection of oilfish‑ and escolar‐derived components. (29th September 2020) - Yao, Lin; Xin, Hongmei; Qu, Meng; Jiang, Yanhua; Guo, Yingying; Li, Fengling; Li, Na; Tan, Zhijun; Wang, Lianzhu
Abstract: BACKGROUND: Oilfish ( Ruvettus pretiosus ) and escolar ( Lepidocybium flavobrunneum ) are often used to adulterate high‐value aquatic products, causing serious economic losses to consumers, and even keriorrhea in severe cases. It was difficult to identify them by morphological features for these two fish were processed into steak or fillet. The purpose of this study, therefore, is to develop an accurate and efficient method for detecting the oilfish‑ and escolar‐derived components. RESULTS: By comparing the mitochondrial 16S ribosomal RNA gene sequences of oilfish, escolar, and 16 varieties susceptible to adulteration, specific primers/probes were designed, and a duplex real‐time polymerase chain reaction (PCR) method was established to detect oilfish‑ and escolar‐derived components. The specificity and sensitivity of the method were analyzed, and the method was used to analyze 70 commercial samples to evalutate its applicability to actual samples in the market. The method developed was highly specific, without any cross‐reaction on the other 16 species, with a limit of detection (LOD) for DNA of 0.0002 ng μL −1 for R. pretiosus and 0.002 ng μL −1 for L. flavobrunneum . In addition, the LOD for mixed muscle tissues was 0.1 g kg −1 . Oilfish‑ and escolar‐derived components were detected in 12 of the 70 commercial samples, a result that is consistent with the classic DNA barcoding test results. CONCLUSION: The duplex real‐time PCR method developed can be used to detect oilfish and escolar specifically, sensitively and accurately; it provides a good technical support for the identification of authentic aquatic products. © 2020 Society of Chemical Industry